Assessing Risk of Victim Crossover with Children and Young People who display Harmful Sexual Behaviours. (26th June 2013) - Allardyce, Stuart; Yates, Peter Michael
Abstract : Assessments of children and young people who display harmful sexual behaviours need to consider – at a broad level – the safety of other children at home, in the community and in the wider family. To date, issues of victim selection have been marginalised in the relevant literature. Drawing on our experience of working with this client group, this article uses four composite case studies that reflect the heterogeneity of children and young people who sexually abuse and applies recent research findings about intra‐ and extra‐familial sexual abuse to make suggestions for good practice in assessment and intervention with young people who display harmful sexual behaviours in different settings. Copyright © 2013 John Wiley & Sons, Ltd. 'Issues of victim selection have been marginalised in the relevant literature' Key Practitioner Messages: Young people with harmful sexual behaviour are a heterogeneous group who may be more likely than adults to vary victim type. A formulation approach to risk assessment allows us to move beyond merely the likelihood of future risk, to consider more dynamically issues of victim selection and circumstances in which risks may present. Assessments of family relationships, in particular sibling relationships, can help sharpen our approach to risk assessment and the potential for family‐community crossover.